Effects of State Degeneration in 3D Quantum Lenoir Engine Performance - Ade Fahriza; Trengginas E. P. Sutantyo (Jurnal Ilmu Fisika, 2022)
We study the performance of the quantum Lenoir engine using single-particle confined within the cubic potential. In 3D potential structure, particles degenerate into multiple states at identic energy level which occurs on the excitation state of the particles. Deliberating the degeneration effects, the confined particle has possibility to produce more energy efficiency as engine’s working substance. The particle is able to freely move in three directions of x, y, and z-axis simultaneously, which gives three degrees of freedom to the particle in the cubic potential. By limiting to two eigen states, a basic explanation to the condition of the particle was provided. The efficiency of 3D quantum Lenoir engine is better than the classical model of the Lenoir engine despite the similarity in the formulation. Moreover, we also consider the efficiency comparison between the 3D model, with some state modifications, and the 1D efficiency of the quantum Lenoir engine. As expected, degeneration of the particle’s states plays a role in the enhancement of the quantum Lenoir engine’s efficiency. Moreover, we also derived the power output of the 3D quantum Lenoir engine. Thus, this study clearly gives a sight of the performance of quantum Lenoir engine model in the 3D manner.